Analisis Kontribusi Pajak Kendaraan Bermotor, Bea Balik Nama Kendaraan, Pajak Bahan Bakar Kendaraan Bermotor, dan Pajak Air Permukaan Terhadap Penerimaan Peningkatan Pendapatan - Maura Yuanitha; Meidy Lieke Karundeng (Cv. Syntax Corporation Indonesia, 2023)
This study aims to determine the contribution of four types of taxes, namely PKB, BBNKB, PBBKB, and PAP, to the province of West Java in the period 2015-2022. This study uses a quantitive descriptive method by taking secondary data from 2015-2022. The results of the study showed that PKB had a relatively good impact on PAD, BBNKB had a less good impact on PAD, and PAP had a very low impact on PAD. However, the growth rate of PKB continued to increase, while BBNKB, PBBKB, and PAP declined. The study suggests that there needs to be good cooperation between taxpayers and tax officials to improve the contribution of these taxes to PAD.